Exploring firm-community level trust in rural Africa through the lens of oil companies' corporate social responsibilities. Issue 3 (15th February 2021) - Meribe, Nnaemeka Chidiebere; Ayentimi, Desmond Tutu; Oke, Benson Reuben; Adonteng-Kissi, Obed
Abstract : Purpose: This paper aims to explore firm-community level trust in rural Africa through the lens of oil companies' corporate social responsibilities (CSR). Design/methodology/approach: This paper is grounded on a case study of local communities and other stakeholders in a Nigerian community exploring the underlying triggers of distrust and trust between oil companies and rural communities through the lens of CSR. Findings: This exploratory study found the presence of high-level firm-community expectation differentials, pointing to considerable mistrust between local communities and oil companies' CSR initiatives. Practical implications: The local communities tend to feel oil companies attempt to secure social licence to operate by engaging in CSR initiatives but not to genuinely improve their welfare. There is, therefore, a superficial effort or incentive for oil companies to engage in CSR initiatives in rural Africa. Originality/value: The paper highlights the notion that building a community-driven CSR requires a partnership in which local communities share legitimacy with government agencies and oil companies in influencing CSR initiatives. This represents the most effective way of enhancing firm-community level trust and social legitimacy in rural Africa.